Spiking neural P systems with anti-spikes and without annihilating priority working in a 'flip-flop' way. (1st January 2013) - Tan, Gangjun; Song, Tao; Chen, Zhihua; Zeng, Xiangxiang
Spiking neural P systems with anti-spikes (ASN P systems, for short) are a variant of spiking neural P systems, which are inspired by inhibitory impulses/spikes in biological neural systems. In general ASN P systems, spikes and anti-spikes can annihilate with each other when they meet in a neuron. The annihilation has priority to using spiking and forgetting rules, and takes no time to finish. In this work, we consider ASN P systems without annihilating priority with neurons working in a 'flip-flop' way, that is each neuron can only produce spikes by anti-spikes or produce anti-spikes from spikes. As results, such systems achieve the Turing completeness as number generator. This gives a positive answer to an open problem left in IJCCC (2009, Vol. IV, No. 3, pp.273–282).